Diminish muscle activity by changing an anthropometry data with appropriate workstation among workers in aerospace manufacturing industry - Seri Rahayu , Kamat; Norhidayah, Hashim; Mohd Shahrizan, Othman (2014)
.In the new era of world industrialization, ergonomics plays an important role to improve occupational safety and health, and productivity in most industries including aerospace manufacturing industry. However, aerospace manufacturing industry in Malaysia does not put any priority on ergonomics awareness, for an example, by not selecting a suitable workstation with operators’ anthropometry. As a consequence, operators are exposed to various ergonomic risk factors and prone to have ergonomic injuries. The objectives of this study are to diminish muscle activity while operators perform lay-up process in a workstation, before and after the workstation is changed using suitable an anthropometry data among operators. The surface Electromyography (sEMG), a set of anthropometry ruler and Rapid Upper Limb Assessment (RULA) from Computer-Aided Three-Dimensional Interactive Application (CATIA) software are used to evaluate muscle activity, operators’ anthropometry data, and working posture respectively. Results of muscle activity and RULA found that by changing the anthropometry data with suitable workstation has diminished the physiological stress such as work/loading in muscles as well as extreme posture. The study concluded that suitable operators’ anthropometry must work with appropriate size of workstation because inappropriate selection can contribute significantly to improve physiological performance of the operators.